Dekonstruksi Maskulinitas Tokoh Utama dalam Novel Dilan 1990: antara Romantisme dan Kekerasan serta Implikasinya terhadap Pembelajaran Prosa di SMA - Sintia Wulan Dari; M. Badrus Solichin (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study aims to analyze the construction and critical reading of masculinity in the character of Dilan in Dilan 1990, a novel by Pidi Baiq, by highlighting the tension between romanticism and violence in gender relations. Employing a qualitative descriptive approach, the research applies close reading techniques to dialogues, narrative descriptions, and the character’s actions, grounded in R. W. Connell’s theory of hegemonic masculinity. The findings indicate that Dilan represents hegemonic masculinity through dominant attitudes, emotional control, and possessive behavior toward Milea, which implicitly positions women in a subordinate role within romantic relationships. However, a critical reading of the text also reveals internal contradictions in Dilan’s character, such as expressions of affection, care, and respect toward the maternal figure, reflecting an alternative form of masculinity. The tension between these representations suggests that masculinity in the novel is not singular but socially constructed and shaped by cultural norms and gender discourse of the 1990s. This study affirms that popular literature plays a strategic role in reproducing as well as problematizing gender values in society. Therefore, the findings have implications for teaching prose in senior high schools by promoting gender-critical literacy to foster students’ awareness of healthy and equitable romantic relationships.